KARAKTERISTIK FISIK FILM WHEY DENGAN PENAMBAHAN MINYAK ATSIRI KULIT LEMON - Fahrullah Fahrullah; Fatimah Fatimah; Djoko Kisworo; Wahid Yulianto; Bulkaini Bulkaini; Sukirno Sukirno; Baiq Rani Dewi Wulandani (Faculty of Animal Husbandry, University of Mataram, 2026)
Efforts to improve food quality, particularly those emphasizing sustainability and health aspects, have become a major focus in the food processing industry. This study aimed to determine the effect of different concentrations of lemon peel essential oil on the physical characteristics of whey-based films. The research was conducted using a Completely Randomized Design (CRD) with three replications. The treatments consisted of varying concentrations of lemon peel essential oil: 0% (L1), 2% (L2), and 4% (L3). Data were analyzed using Analysis of Variance (ANOVA), and when significant differences were observed, further analysis was performed using Duncan’s Multiple Range Test (DMRT). The results showed that the addition of essential oil had no significant effect (P>0.05) on film thickness and elongation, but had a significant effect (P<0.05) on tensile strength. The thickness values ranged from 0.14 to 0.16 mm, elongation ranged from 62.10% to 62.77%, and tensile strength ranged from 5.20 to 5.51 MPa. Increasing the concentration of essential oil tended to decrease the tensile strength of the film due to disruption of intermolecular protein interactions and the formation of a discontinuous phase within the film matrix. Meanwhile, the plasticizing effect of the essential oil contributed to increased film flexibility at certain concentrations, although it did not meet the minimum elongation standard. Thus, the addition of lemon essential oil affects the mechanical properties of whey-based edible films, particularly by reducing tensile strength.